Impacts of Moso bamboo (Phyllostachys pubescens) invasion on species diversity and aboveground biomass of secondary coniferous and broad-leaved mixed forest - Chen, Xi; Chen, Xin; Huang, Shiqi; Fang, Dongming (Frontiers in Plant Science, 2022)
In recent decades, moso bamboo has been largely increasing in the subtropical area of China, raising ecological concerns about its invasion into other native forest ecosystems. One concern is whether the invasion of moso bamboo significantly simplifies forest community composition and structure and declines biomass. This paper adopted the space-for-time method to investigate a secondary coniferous and broad-leaved mixed forest (SF) being invaded by an adjacent moso bamboo forest (MB) in Wuxie forest reserve, Zhejiang Province. Three plots were established in each SF, MB, and transitional forest. The results showed that the species composition and species dominance of the arborous layer changed significantly (P<0.05), which was indicated by the significantly decreased species richness (Margalef index, Shannon-Wienner index, and Simpson index) and evenness (Pielou evenness index). In contrast, the species richness of the shrub and herbaceous layers had two divergent indications (increasing or unchanged), and the evenness remained unchanged. The total and arborous-layer aboveground biomass of the forest community has no noticeable change (P<0.05). However, the biomass of the shrub and herbaceous layers showed an increasing trend (shrub significant but herbaceous not), but they only occupied a small proportion (~1%) of the total biomass. At last, the aboveground biomass and the diversity index had no significant correlation in each layer and overall stands. We hope the findings could provide a theoretical basis for the invasion mechanism and the ecological aftereffect of moso bamboo invasion.